The Implementation of Child-Friendly School Innovation in Al Azhar Islamic Elementary School 60 Pekalongan (Educational Management, 2021)
Child-Friendly Schools are defined as competent educational units to guarantee, accomplish, accepting children's rights, as well as protect them from violence, discrimination, and other mistreatments and support children's participation, particularly in planning, policy, learning, and assessment mechanisms. The goal of establishing child-friendly schools is to safeguard and provide educational services that protect children from physical and non-physical violence. With appropriate management, a child-friendly school innovation program will undoubtedly result in an exceptional school and become a community favorite. Al Azhar 60 Islamic Elementary School Pekalongan is one of the schools that has adopted an innovative child-friendly school program, earning it an award from the Pekalongan City government with the main as the best practice school in Pekalongan City for the primary category. This study was qualitative research with a phenomenological approach. In data collection, the researcher employed the triangulation method (in-depth interviews, observation, and documentation) and read related books by using a qualitative approach. It prioritizes data collection or the real problem based on the disclosure of what has been explored by the respondent. The data was collected in the form of written or spoken words from the people observed (Sugiono, 2006). The data analysis was referred to the Miles and Huberman model, namely by collecting data, reducing data, and presenting data. The results of the study show that the implementation of child-friendly school innovation program in SD Islam Al Azhar 60 Pekalongan refers to child-centered activity programs by concerning with children’s characteristics and needs, understanding their diversity and participation, the process of developing students’ learning environment, and the involvement of their parents or which represents and the community who support learning process in the school by having innovation programs, namely Strengthening Characters (Adab: arabic language) Education, Psychology Service Unit and Counseling Guidance, Canting Program and Share Lova Children's Podcast.